Next-Generation Metal Anticancer Complexes: Multitargeting via Redox Modulation - Romero-Canelón, Isolda; Sadler, Peter J. (Inorganic chemistry, 2013)
Platinum complexes are widely used anticancer drugs. New generations of metal chemotherapeutics offer the prospect of combating platinum resistance and expanding the range of treatable cancers. Such new complexes might be effective if they form distinctly different lesions on DNA. In this Forum Article, we discuss the possibility that targeting the redox balance in cancer cells may also be a highly effective strategy, especially because it is a multiple-site approach and offers selectivity over normal cells. Metal complexes can interfere in cellular redox chemistry in several ways: directly through metal or ligand redox centers or indirectly by binding to biomolecules involved in cellular redox pathways. We illustrate that a surprisingly large number of active metal anticancer agents have a potential redox arm to their mechanism of action. For such complexes, the possibility arises of using combination therapy together with redox modulators to increase the anticancer potency: attractive for lowering the doses of metal complexes that need to be administered. We illustrate that organometallic ruthenium(II) and osmium(II) arene complexes and iridium(III) cyclopentadienyl complexes of the type [(arene/CpxPh)M(N,N)Cl/I] n+ can achieve nanomolar potency toward cancer cells in combination with the redox modulator l-buthionine sulfoximine. Our discussion highlights the importance of determining not only the distribution of metal anticancer complexes in cells but also their speciation, the chemical form of the metal complex, including the oxidation state of the metal, the fate of the ligands, and dynamic processes such as efflux. This will be aided in the future by proteomic and genomic analyses but needs to be supplemented by new analytical methods that have the sensitivity and spatial and temporal resolution to reveal such information. To achieve this, major new funding programs are needed that support global research on the design of novel metal-based drugs with new mechanisms of action, tailored to patient needs.